The Impact of Earnings Persistence and Growth Opportunities on the Relevance of Accounting Earnings in Manufacturing Companies of the Pulp and Paper Sub-Sector Listed on the Indonesia Stock Exchange (IDX) in 2020-2025 - Putra, Dori HP (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to determine: 1) Whether there is an influence of Earnings Persistence and Growth Opportunities on the Relevance of Accounting Earnings (ERC) in the Manufacturing Companies of the Pulp and Paper Sub-Sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2025, both partially and simultaneously? 2) The extent of the influence of Earnings Persistence and Growth Opportunities on the Relevance of Accounting Earnings (ERC) in the Manufacturing Companies of the Pulp and Paper Sub-Sector listed on the Indonesia Stock Exchange (IDX) from 2020 to 2025. The analytical tool used in this study is multiple linear regression analysis with the aid of SPSS version 26. The data source is from annual financial reports. Data collection is done through the library research technique. The methods used are both quantitative and qualitative. The quantitative method is used for observation involving numerical calculations, while the qualitative method is used to analyze financial data within the companies by referring to relevant theories or concepts.